Classification of thermal ageing impact of ester fluid‐impregnated pressboard material adopting LIBS. Issue 4 (20th March 2021) - Amalanathan, Arputhasamy J.; Vasa, Nilesh J.; Harid, Noureddine; Griffiths, Huw; Sarathi, Ramanujam
Abstract: This article reports the thermal ageing of ester fluid‐impregnated pressboard material along with its performance evaluation using optical emission spectroscopy (OES) and classification using machine‐learning algorithms adopting laser‐induced breakdown spectroscopy (LIBS). The surface discharge analysis on ester‐impregnated pressboard (EIP) is studied using OES and the plasma temperature was evaluated based on the Cu I emission lines which were higher under the negative DC compared with the positive DC and AC voltages. The LIBS analysis was performed on the EIP material operated at different energy levels in order to acquire the optimal energy required to be used for its classification algorithm. The intensity ratio and electron density evaluated from LIBS studies correlated well with the plasma temperature. The lower limit of detection (LOD) calculated based on linear regression analysis for copper peak was around 3.5 times higher than the identification of carbon peak. The machine‐learning techniques like principal component analysis and neural network algorithm have been performed on the LIBS spectral dataset in order to classify the ageing of EIP material. Artificial neural network adopting LIBS provided a better classification accuracy on all the aged samples compared with principal component analysis which classified only for the samples aged at higher temperatures.